THE DEVELOPMENT OF CHILDREN'S FITRAH IN THE PERSPECTIVE OF ISLAMIC EDUCATION AND ITS APPLICATIONS TO THE CASE OF CONFLICT BETWEEN CHILDREN'S FITRAH AND PEOPLE'S DESIRES - Fatimah , Rosyada Ayu; Mailandari , Olvy; Sutipyo, Sutipyo (Journal of Islam and Science, 2022)
This paper aims to find out the meaning of fitrah, and to solve cases of hampered development of children's fitrah due to parental demands that are contrary to the innate potential, passion, and habits of their children. The problem of developing fitrah in children is an urgent matter and requires prioritized attention. According to Al-Ghazali, a child has an innate fitrah from birth, namely the nature towards the good or the bad. For this reason, the role of parents, teachers, and the environment is needed to shape the potential of children into good nature, based on 2 sources of Islamic law, namely the Qur'an and Al-Sunnah. The purpose of developing children's nature in a good direction is to form generations who are intellectually and spiritually intelligent.